Sarkoma Ewing: Diagnosis dan Tatalaksana - Hisbul Waton; Helmi Ismunandar; Oktadoni Saputra; Ratna Dewi Puspita Sari (Medula, 2023)
Ewing's sarcoma (ES) is the second most common bone malignancy. It is accompanied by osteosarcoma. Ewing's sarcoma is most common in people between the ages of 10 and 20, or becomes more common in their 20s, and most cases affect males. The exact cause of Ewing's sarcoma is unknown, but it is currently associated with a translocation of chromosomes 11 and 12 which results in fusion of the EWS and FL-1 genes in 90% of cases. Ewing's sarcoma is often diagnosed with an extensive lesion and metastases, so the patient's prognosis is poor. Complaints that are often found in patients with Ewing's sarcoma are pain, fever, mass and fracture pathology. In addition, laboratory tests found an increase in blood sedimentation levels (ESR), anemia followed by an increase in white blood cells, lactate dehydrogenase (LDH). Radiographs show ill-defined, punctate, penetrating, or moth-eaten lesions, onion-like periosteal reaction, and abundant soft tissue around the diaphysis or metaphysis. Treatment of Ewing's sarcoma is a multimodal approach that combines chemotherapy, physical therapy, and radiation therapy. This combination has been shown to increase the 5-year survival rate of patients with Ewing's sarcoma to over 50%.